1987
DOI: 10.1152/ajpcell.1987.253.1.c30
|View full text |Cite
|
Sign up to set email alerts
|

Na-H and Cl-HCO3 exchange in rabbit oxyntic cells using fluorescence microscopy

Abstract: We have used the fluorescence intensity ratio (excitation 490/439; emission 520-550 nm) of 2',7'-bis(carboxyethyl)-5(6)-carboxyfluorescein (BCECF) to measure intracellular pH (pHi) in single oxyntic cells (OCs) within intact gastric glands isolated from rabbits. The fluorescence ratio was converted to pHi by exposing cells to high [K] Ringer plus 10(-5) M nigericin. Ratios varied linearly with pHi over the physiological range. When the bathing solution was changed from NaCl to Na gluconate Ringer, pHi increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
1

Year Published

1989
1989
2008
2008

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 17 publications
3
17
1
Order By: Relevance
“…In the histamine-stimulated cells, when it is expected that the Cl channels in the apical membrane have been activated (Demarest et al, 1989), there was still good agreement between the Cl fluxes (70 mM/min) and the HCO3 fluxes (77 mM/min). In addition, it has been shown previously that 200-500 ,uM H2DIDS largely blocks the Cl-induced changes of pHi (Paradiso et al, 1987), and the present experiments have shown that Cl fluxes were blocked by -80% (Figure 9). The close agreement among these measurements indicates that during changes of Clo, influx and efflux of Cl from the cell are mediated primarily through the anion exchanger that is present in the basolateral membrane.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the histamine-stimulated cells, when it is expected that the Cl channels in the apical membrane have been activated (Demarest et al, 1989), there was still good agreement between the Cl fluxes (70 mM/min) and the HCO3 fluxes (77 mM/min). In addition, it has been shown previously that 200-500 ,uM H2DIDS largely blocks the Cl-induced changes of pHi (Paradiso et al, 1987), and the present experiments have shown that Cl fluxes were blocked by -80% (Figure 9). The close agreement among these measurements indicates that during changes of Clo, influx and efflux of Cl from the cell are mediated primarily through the anion exchanger that is present in the basolateral membrane.…”
Section: Discussionsupporting
confidence: 83%
“…Intracellular signaling events ultimately lead to the transition from the resting to the stimulated state. An H/ K-ATPase is activated in parallel with permeability pathways for both Cl and K on the apical canalicular face of the PC, whereas an anion exchanger provides pathways for Cl entry and HCO3 exit on the basolateral side of the cell (Ito and Schofield, 1974;Lee et al, 1979;Forte et al, 1981;Wolosin and Forte, 1984;Muallem et al, 1985Muallem et al, , 1988Paradiso et al, 1987; Ueda et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…However EBF was 28 pmol/min per mm in HCO , which was similar to the result obtained in Hepes. Therefore, exogenous HCO-failed to stimulate apical CF/ base exchange in contrast to the stimulation of Cl-/base exchange by HCO-reported in other cell types (15,16,(43)(44)(45)(46)(47). The lack of stimulation of apical Cl -/base exchange could have been due to enhanced basolateral base efflux in HCO--containing solutions.…”
Section: Discussioncontrasting
confidence: 60%
“…G astric acid production originates in the parietal cell through the coordinated operation of apical and basolateral membrane transport proteins (1)(2)(3)(4)(5)(6)(7)(8)(9). The apical secretory machinery includes the gastric H-K-ATPase, a chloride channel, and a K ϩ recycling pathway (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…The apical secretory machinery includes the gastric H-K-ATPase, a chloride channel, and a K ϩ recycling pathway (1)(2)(3)(4)(5)(6)(7)(8)(9). Despite an essential role for the apical Cl Ϫ channel in gastric acid secretion, its molecular identity remains unknown.…”
mentioning
confidence: 99%